(untitled) (Annals of Medical Research, 2021)
Aim: In this article, we evaluated risk factors associated with cardiac surgery-related AKI, including the pathophysiology, potential causes of injury, and preventing modalities.Acute kidney injury (AKI) is a significant obstacle that is of remarkable attention after cardiac surgical procedures. Perioperative AKI is independently correlated with an increase in morbidity, costs of treatment, prolonged hospitalization and increase in mortality.Material and Methods: Two hundred and nineteen patients who underwent coronary artery bypass grafting surgery from April through June 2019 were enrolled in this prospective study. Left ventricle ejection fraction, complete blood count, and kidney function test (KFT) were evaluated preoperatively. And, in perioperative evaluation, aortic cross-clamp time, minimum hemoglobin value, and mean arterial pressure, the perioperative fluid type used were recorded. KFT were recorded at postoperatively and, patients with AKI were identified using Kidney Disease Improving Global Outcomes classification.Results: Left ventricle ejection fraction of the patients who did not have AKI was significantly higher (p=0.009). A higher rate of AKI was observed in perioperative colloid used patients (p=0.004). Perioperative MAP values were significantly lower in patients having AKI (p=0.002). There is also a positive correlation between the decrease in MAP value and the development of AKI. Conclusion: Improving factors effecting arterial blood flow of the kidney such as preoperative hemoglobin value, perioperative mean arterial pressure may restrain the risk of cardiac surgery-related AKI. Also, we found that the use of colloid solutions while cardiac surgery was associated with more AKI. Based on this result; it is crucial managing perioperative fluid therapy more targeted and considering the personal data of the patients.